Cyclin-Dependent Kinase 5 Regulatory Subunit Associated Protein 3: Potential Functions and Implications for Development and Disease - Sheng, Linna; Li, Jiaxuan; Rao, Shengfang; Yang, Zhijun; Huang, Yonghong (Frontiers in Oncology, 2021)
Cyclin-dependent kinase 5 (CDK5) regulatory subunit associated protein 3 (CDK5RAP3, also named as C53 or LZAP) was initially identified as a binding protein of CDK5 activator p35. Published research has revealed that CDK5RAP3 interacts with a range of proteins. Probably owing to its extensive interactions, CDK5RAP3 has been demonstrated to modulate a variety of cellular events ranging from cell cycle, apoptosis, adhension, invasion to signal transduction, as well as autophagy, UFMylation modification and endoplasmic reticulum stress. Meanwhile, genetic research demonstrates CDK5RAP3 is essential for embryoic and mammalian development. Furthermore, CDK5RAP3 has been reported to be association with various human cancers such as head and neck squamous cell carcinoma, gastric cancer, hepatocellular cancer, lung cancer, kidney cancer and breast cancer. Notwithstanding, the detailed function of CDK5RAP3 and its mechanism remain poorly defined, and it also exhibits controversial effects on human cancers to date. Here, we first introduce the discovery of CDK5RAP3, the structure and localization features of CDK5RAP3. Then we focus on the possible functions of CDK5RAP3 and its implications for development and disease. This review may facilitate to understand the molecular and functional basis of CDK5RAP3 and its association with development and disease, and provide a reasonable idea for novel therapeutic opportunities targeting CDK5RAP3 in either cancer or other diseases.